ClC-7 expression levels critically regulate bone turnover, but not gastric acid secretion - C. Supanchart (2018)
Mutations in the 2Cl - /1H + -exchanger ClC-7 impair osteoclast function and cause different types of osteoclast-rich osteopetrosis. However, it is unknown to what extent ClC-7 function has to be reduced to become rate-limiting for bone resorption. In osteoclasts from osteopetrosis patients expression of the mutated ClC-7 protein did not correlate with disease severity and resorption impairment. Therefore, a series of transgenic mice expressing ClC-7 in osteoclasts at different levels was generated. Crossing of these mice with Clcn7 -/- mutants rescued the osteopetrotic phenotype to variable degrees. One resulting double transgenic line mimicked human autosomal dominant osteopetrosis. The trabecular bone of these mice showed a reduction of osteoblast numbers, osteoid, and osteoblast marker gene expression indicative of reduced osteoblast function. In osteoclasts from these mutants ClC-7 expression levels were 20 to 30% of wildtype levels. These reduced levels not only impaired resorptive activity, but also increased numbers, size and nucleus numbers of osteoclasts differentiated in vitro. Although ClC-7 was expressed in the stomach and PTH levels were high in Clcn7 -/- mutants loss of ClC-7 did not entail a relevant elevation of gastric pH. In conclusion, we show that in our model a reduction of ClC-7 function by approximately 70% is sufficient to increase bone mass, but does not necessarily enhance bone formation. ClC-7 does not appear to be crucially involved in gastric acid secretion, which explains the absence of an osteopetrorickets phenotype in CLCN7-related osteopetrosis. © 2013 Elsevier Inc.